2021
DOI: 10.3390/socsci10030099
|View full text |Cite
|
Sign up to set email alerts
|

Got Skillz? Recasting and Negotiating Racial Tension in Teacher–Student Relationships Amidst Shifting Demographics

Abstract: This paper reports on a curriculum designed for Black students whose school teachers and administrators sought to address concerns about students’ academic underachievement and behavioral challenges. In order to design the curriculum, we examined Black students’ reactions to race- and academic-related stress as a result of their interactions with mostly White teachers and peers in an increasingly diversifying predominantly White, middle-class community. Grounded in principles of Racial Encounter Coping Apprais… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 100 publications
(169 reference statements)
0
4
0
Order By: Relevance
“…We are also seeing innovations in treatments for youth experiencing racism that build on the racial socialization framework mentioned earlier (e.g., Anderson et al, 2019; Metzger et al, 2021). Similar approaches for mitigating the effects of racism, discrimination, and harsh discipline practices are being extended to schools (e.g., Coleman-King et al, 2021; Okonofua et al, 2022) and early childhood settings (Schoch & Gal-Szabo, 2023).…”
Section: The Way Forwardmentioning
confidence: 99%
“…We are also seeing innovations in treatments for youth experiencing racism that build on the racial socialization framework mentioned earlier (e.g., Anderson et al, 2019; Metzger et al, 2021). Similar approaches for mitigating the effects of racism, discrimination, and harsh discipline practices are being extended to schools (e.g., Coleman-King et al, 2021; Okonofua et al, 2022) and early childhood settings (Schoch & Gal-Szabo, 2023).…”
Section: The Way Forwardmentioning
confidence: 99%
“…Specifically, some Black parents reported that remote learning buffered their children from being targeted for disciplinary infractions (Miller, 2021 ; St. George, 2021 ). Black children must navigate racial discrimination in school and manage racial encounters with students and teachers while tasked with learning (Bentley‐Edwards et al, 2020 ; Coleman‐King et al, 2021 ). Black girls, for example, are adultified by their teachers, and often described as loud and unruly, while their self‐advocacy is interpreted as aggression or anger (Adams‐Bass, 2021 ; Adams‐Bass & Bentley‐Edwards, 2020 ; Butler‐Barnes & Inniss‐Thompson, 2020 ; Morris, 2007 ).…”
Section: Consequences Of Covid‐19 At the School Levelmentioning
confidence: 99%
“…While we advocate for a whole school approach, principles from the STARS blueprint can also be applied within courageous conversations where they interrogate their assumptions about race and culture and how those assumptions impact students and the overall school racial climate (Howard, 2020). Several programs and interventions across the pedagogical and psychological literature promote conversations and training to address race in schools (e.g., Coleman-King et al 2021;Picower, 2021;Stevenson, 2014) so that staff feel better prepared to address such topics, respond to race-based incidents, and promote positive adjustment for youth. Along these lines, we advocate for the incorporation of existing or developing best practices in talking about race and utilizing RES strategies, including tools and interventions to increase self-efficacy, competency, skills, and confidence (Anderson & Stevenson, 2019;Stevenson, 2014).…”
Section: Implications For Embedding Equity Into School Mental Healthmentioning
confidence: 99%